The Ribeirão Preto Metropolitan Region: allocation of financial resources to SDGs - Gomes, Erasmo José (2024)
The present work aims to propose a method for identifying and measuring the allocation of financial resources, between 2016 and 2020, by the 34 municipalities in the Ribeirão Preto Metropolitan Region (RPMR) to achieve the Sustainable Development Goals (SDGs). To test the suitability of the proposed method for the intended objective, SDG 11 was selected – inclusive, safe, resilient, and sustainable cities and communities. As a result of the application of the proposed method, it was possible to highlight, in terms of the volume of allocated financial resources, the relative importance or priority attributed by the RPMR municipalities to meeting the SDGs, in particular, SDG 11. Thus, it was found that the goals 11.1, 11.3, and 11.a represented 78.7% of the total expenditure. DOI: https://doi.org/10.1590/2236-9996.2024-6154505-pt https://doi.org/10.1590/2236-9996.2024-6154505-en